Contribution to the knowledge of two endemic species of Anatolian Gomphocerinae Fieber, 1853 (Orthoptera: Acrididae) - Mol, Abbas; Taylan Mehmet Sai̇t; Şi̇ri̇n Deni̇z (Zootaxa, 2015)
This study focuses on two endemic Anatolian Gomphocerinae Fieber, 1853 species, which are evaluated in terms of nomenclature and taxonomy using biogeographical, morphological, and acoustical data. The original description of Eremippus zeybekoglui is supplemented by the data on new specimens collected from type locality, and the female of this species is described for the first time in this study. Based on the new specimens of Stenobothrus weidneri (Demirsoy, 1977) comb. nov., which were collected at the type locality, the species is transferred from Eremippus Uvarov, 1926 to Stenobothrus Fischer, 1853. Additionally, male calling songs of both species are described for the first time in this study. Also, the biogeography of these species is presented and discussed.